Protestant Periodicals in Transition: From the Twentieth Century to the Digital Age - Bassimir, Anja-Maria; Gelfgren, Stefan (Studies in Periodical Cultures, 2023)
Protestant Periodicals in Transition: From the Twentieth Century to the Digital Age demarcates the field of religious periodical studies by offering a range of historical and contemporary case studies from different Protestant traditions drawn from various regions of the world. Taking religion, periodicals, and their cultures seriously, this volume focuses not only on content but on the people, processes, networks, technologies, and economics involved in periodical publishing. Case studies explore the role of the Protestant magazine in defining, policing, and extending the boundaries of religious communities, of engaging with and influencing the surrounding society through political activism and lifestyle advice, and adapting to and sometimes spearheading technological changes to keep relevant in changing times